Baseline geophysical data for hazard management in coastal areas in relation to earthquakes and tsunamis. Issue 1 (April 2016) - Murthy, KSR
A systematic study of geophysical data of the Eastern Continental Margin of India was taken up to identify the land–ocean tectonic lineaments over the east coast of India and the possible neotectonic activity associated with them. These studies helped in delineating the offshore extension of some of the coastal lineaments. Analysis of magnetic, gravity and shallow seismic data, combined with reported seismicity data, indicates moderate seismicity associated with some of these land–ocean tectonics of the Eastern Continental Margin of India. The coastal/offshore regions of Vizianagaram (north of Visakhapatnam) and Ongole of the Andhra Pradesh margin and the Puducherry shelf of the Tamil Nadu margin have been identified as zones of weakness where neotectonic activity has been established. Bathymetry data over the Eastern Continental Margin of India revealed the morphology of the shelf and slope of this margin, which in turn can be used as the baseline data for tsunami surge models. Detailed bathymetry map and sections of the Nagapattinam–Cuddalore shelf (from 10.5° to about 12°N) indicate that one of the main reasons for the higher run-up heights and inundation in the Nagapattinam–Cuddalore coast during the Indian Ocean Tsunami of 26 December 2004 could be the concave shape of the shelf with a gentle slope, which might have accelerated the tsunami surge to flush through at a rapid force. Structural control also appears to be a contributing factor for the tsunami surge.